Pengembangan Sistem Informasi Manajemen Presensi Kegiatan Ibadah Siswa berbasis Website (Studi pada: SMK Muhammadiyah 1 Malang) - Tio Rizky Bachtiar; Satrio Agung Wicaksono; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
SMK Muhammadiyah 1 Malang is an educational institution that upholds religious values by including worship activities as mandatory activities. Worship activities must be carried out every day by all students. The teacher always supervises every worship activity carried out by students by incorporating the value of student worship into the presence of worship. With the number of students and activities that must be recorded by the teacher, a problem arises, namely the teacher always has difficulty in managing the attendance recap of students' worship to become the final grade when the end of the semester arrives. Responding to these problems, researchers are trying to create a presence information system that is useful for solving problems that are currently happening. The information system that will be built is website-based by utilizing the Laravel Framework for its Back-End, while the implementation will be in the form of Mobile Apps and Desktop Apps by utilizing the Vue.js Framework.